PERANCANGAN BPF CAUER-CHEBYSHEV PITA SEMPIT UNTUK APLIKASI SAR BERBASIS FMCW - Zainal Abidin; Achmad Munir (SENTIA 2016, 2016)
It is known that synthetic aperture radar (SAR) was commonly used to obtain a high image resolution of radar detection. Therefore, supporting devices for SAR are almost required. This research is proposed to design bandpass filter (BPF) Cauer-Chebyshev for SAR application. Signal types and techniques of signal generation are important things in the design of the filter. Here, frequency modulated continuous wave (FMCW) method with narrowband response is used as a modulation technique for SAR. Whilst, wideband response was rarely used due to a great attenuation affected by atmosphere. In the design, it shows that the filter is made from lumped elements with Cauer-Chebyshev type of order 5 with the passband area of 25-35MHz. The result demonsrates that the filter has the minimum S11value of -0.274dB at the passband area of of 25-35MHz and the maximum S21 value with ripple of -12.141dB at the passband area of of 25-35MHz. It indicates that the value of S21 at the passband area of of 25-35MHz is almost constant. In adiition, it shows that the filter has a transition area quite narrow but with high complexity on its circuitry.